4′-Phenyl-2, 2′:6′, 2″-terpyridine derivatives-synthesis, potential application and the influence of acetylene linker on their properties. (November 2017) - Zych, Dawid; Slodek, Aneta; Matussek, Marek; Filapek, Michał; Szafraniec-Gorol, Grażyna; Maślanka, Sławomir; Krompiec, Stanisław; Kotowicz, Sonia; Schab-Balcerzak, Ewa; Smolarek, Karolina; Maćkowski, Sebastian; Olejnik, Marian; et al.
Abstract: Novel derivatives of 4'-phenyl-2, 2':6′, 2″-terpyridine (tpy) with ethynyl (T1 ), 2-ethynyl-9, 9-dioctylfluorene (T2 ), 9, 9-dioctylfluorene (T3 ), 9-ethynyl-10-decyloxyanthracene (T4 ) substituents were obtained via Sonogashira or Suzuki-Miyaura coupling reactions, respectively, and thoroughly characterized. The presence of ethynyl bridge impacts photophysical properties of novel compounds by shifting absorption and emission spectra towards longer wavelengths as compared toT3, where fluorene is connected with tpy via a single bond. TGA measurements showed that among the new terpyridines those obtained as solids exhibited high thermal stability as opposed to those which were oils (tpy containing fluorene motif). Due to the fact that high thermal stability of 4'-phenyl-2, 2':6′, 2″-terpyridine derivatives showed photoluminescence (PL) quantum yield (Φ) in the range of 27–84% in solution, their electroluminescence ability was tested in diodes with guest-host configuration. For the compounds dispersed in a matrix consisting of poly(9-vinylcarbazole) (PVK) (50 wt %) and (2- tert -butylphenyl-5-biphenyl-1, 3, 4-oxadiazole) (PBD) (50 wt %) radiation with maxima between 374 and 531 nm and characterized with Φ in the range of 8–12% was observed. They exhibited green or violet electroluminescence. The results confirmed the substantial role of aryl groups and the linker in the presented terpyridines in terms of their thermal, electrochemical, optical and electroluminescence properties. In addition, density functional theory (DFT) and time-dependent-density functional theory (TD-DFT) calculations were performed to provide an independent support and deeper insight into the experimental results. Graphical abstract: Highlights: Novel and well-soluble derivatives of 4′-phenyl-2, 2′:6′, 2″-terpyridine were obtained. The influence of acetylene linker on thermal, electrochemical, optical and electroluminescence properties was examined. Efficient luminophores with high photoluminescence (PL) and quantum yields (Φ). OLEDs devices containingT1 andT4 as emitters showed green to orange electroluminescence.